Self-point defect trapping responsible for radiation swelling reduction in V–Ti alloys. (April 2021) - Boev, A.O.; Nelasov, I.V.; Lipnitskii, A.G.; Kartamyshev, A.I.; Aksyonov, D.A.
Abstract: The very low swelling of V–Ti alloys under neutron irradiation is a poorly understood phenomenon. To uncover the underlying mechanism of swelling reduction, we performed density functional theory and molecular dynamics simulations with a V-4% Ti random alloy with interatomic potentials. We find that titanium solutes efficiently trap vacancies and self-interstitial atoms. Exceed vacancies conserve their individuality, forming a variety of complexes with Ti solutes compared to their association into a dislocation loop in pure V. Randomly distributed Ti-vacancy complexes are much more appropriate for efficient point defect recombination as opposed to the localized dislocation loop formed in pure V.